Hybrid matrix converter topologies: an exploration of benefits - Klumpner, Christian; Pitic, Cristian (2008)
Matrix converters are direct AC/AC power converters that can operate with sinusoidal output/input voltage/currents without the need of passive components to store energy, which means that they are grid friendly and have a great weight/volume reduction potential. Hybrid power converters are arrangements of two different type of converters, a main one, processing the bulk of the power interconnected with an auxiliary one, more versatile, processing only a fraction of the power, with the purpose of improving the main converter performance and/or mitigate some of its drawbacks. This paper will review a few hybrid matrix converter solutions developed to address the main drawbacks of the matrix converter technology: the limited (≤0.866) voltage transfer ratio and the sensitivity to power supply disturbances.